Neurobrucellosis in Children - Musa Kazim Caglar; Sabiha Aysun (Paediatrica Indonesiana, 1989)
Although the neurological symptoms in brucellosis are frequent, nervous system involvement is uncommon. In addition, blood and cerebrospinal fluid may not show growth of Brucella in culture. For these reasons brucellosis may not be considered hence correct diagnosis of the disease may be delayed. We have presented three cases of leptomeningitis due to brucellosis where diagnosis was delayed one to two months and was correctly made in two cases only after bone marrow aspiration culture.